Comparison of Amniotic Fluid Index and Single Deepest Vertical Pool method for predicting fetal outcome - Shah, Rajiv; Sharma, Paban (Journal of College of Medical Sciences-Nepal, 2017)
Background & Objectives: The measurement of amniotic fluid volume (AFV) has been an important component of antenatal evaluation of fetal well being. The most commonly used methods are by amniotic fluid index technique (AFI) and single deepest pool method (SDVP). Both the methods employ ultrasound for AFV measurement. The objective of this study is to compare the usefulness of AFI and SDVP method in assessing amniotic fluid volume for predicting adverse perinatal outcome. Materials & Methods: This is a hospital based prospective comparative study. The patient whose amniotic fluid was measured by SDVP technique was study group and that by AFI was comparison group. Any case with high risk factor was excluded from the study. First case was decided by lottery and then alternately one case was kept in study group and the other in comparative group. If the women did not deliver within 1 week the measurements was retaken and the final values was used for analysis.AFI was estimated as described by Phelan and colleagues and SDVP as described by Manning. Data collection was started after the approval of Institution review board. This study was conducted at Patan Academy of Health Sciences. Duration of data collection was 3 months, Asadh –Bhadra, 2071. Results: A total of one hundred and fifty four cases which met the inclusion criteria were taken. Incidence of oligohydramnios by SDVP method was 10.4 % by SDVP technique and by AFI method it was 18.2 %. There was no statistical significant difference between the two groups in terms of rate of induction, mode of delivery, meconium staining of liquor, fetal heart rate tracings, APGAR score at 5 mins and admission to special care baby unit. Conclusion: In non-high risk pregnancy AFI technique detects slightly more number of oligohydramnios as compared to SDVP technique without apparently any difference in perinatal outcome.